The effect of work stress on the performance of cabin crew - Mourad Mortada Mustafa Elwezza; Magda Hassan Elbadry; Nashwa Mohamed Talaat (Cairo : Mourad Mortada Mustafa Elwezza, 2013)
Aviation law in the whole world imposes providing professional cabin crew onboard the flights. Their primary role is to ensure the safety of passengers in addition to comfort . They are responsible for the application of safety procedures before during and after the flight in addition to administrating first aid
Thesis (M.Sc.) - Sadat city University - Faculty of Tourism and hotels - Department of Tourism studies